Immediate Dentin Sealing versus Dentin Air Abrasion Prior to Composite Inlay luting Procedures (Medical Forum Monthly, 2021)
Objective: The aim of this in vitro study was to investigate the shear bond of Immediate Dentin Sealing versus dentin air abrasion prior to Composite luting Procedures.Study Design: Comparative StudyPlace and Duration of Study: This study was conducted at the College of Dentistry, Qassim University, Kingdom of Saudi Arabia from January 2019 till December 2020.Materials and Methods: The study design was comprised 30 non carious molars which were divided into three equal groups. The occlusal third of the crowns were cut with a slow-speed diamond saw. The groups were as follows: group A, dentin etched with 35% phosphoric acid for 10 s directly prior to luting procedures. group B, immediate dentin sealing is done directly after cavity preparation. group C, dentin surface was abraded at 60 psi with 50-μm aluminum oxide for 30 sec directly prior to luting procedures. The resin composite inlays were adhered to different treated dentin surface using adhesive resin cement. The specimens with their adhered inlays of each group were subjected to shear bond strength testing. Analysis of the recorded shear bond strength values (Mpa) were done using one-way analysis of variance and Tukey post hoc test. Statistical analysis was performed using Graph pad Prism-6 statistics software for Windows P values ≤ 0.05 are considered to be statistically significant in all testsResults: Mean shear bond strength values are presented in Table1: The shear bond strength values (Mpa) were analyzed using one-way analysis of variance and Tukey post hoc test and were revealed a significant influence of the main groups type tested (p≤ 0.05) on shear bond strength mean values (Group C > group B > group A)Conclusion: Dentin Surface treatment by air abrasion can increase the bond strength of total-etch adhesives. Immediate dentin sealing bonding strength is less than air abraded dentin bond strength.